Peer-Mediated Interventions to Enhance Conversation Skills of Young Adults with Intellectual and Developmental Disabilities on a University Campus - Bross, Leslie Ann; Wall, Emily; Pinczynski, Monique; Anderson, Ashley; Williams, Thai; Wood, Charles L.; Spooner, Fred (Journal of developmental and physical disabilities, 2024)
Young adults with intellectual and developmental disabilities (IDD) on college campuses are vulnerable to exclusion and a lack of social participation. However, peers can provide meaningful supports to young adults with IDD in the area of social/communication skills. The purpose of this study was to enhance the conversation skills of four young adults with IDD (ages 22–23) during their regular lunch breaks on a university campus. The dependent variable was percent of conversational engagement during 10-min audio recorded sessions as measured using partial interval recording procedures. Typically developing peers served as peer coaches and provided structured or natural supports. Experiment 1 used an alternating treatments design to compare the effects of peer coaching alone vs. peer coaching + goal setting with two adjacent baseline conditions and a final student-choice condition. Results for Experiment 1 indicated peer coaching alone and the additive effects of goal setting was more effective than natural supports only. Experiment 2 used a withdrawal design to compare the effects of young adults with IDD speaking with fellow classmates with disabilities vs. peers without disabilities. Participants in Experiment 2 demonstrated higher levels of conversational engagement when speaking with peers without disabilities in a natural manner. Social validity of the different peer-mediated interventions was overall high for all participant types as reported on questionnaires and exit interviews. We provide implications for practice and suggestions for future research related to peer-mediated interventions for young adults with IDD on college and university campuses.